We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+5
447
1
avatar+266 

A= [-3  5  -6

       9  -5  3]

 

B=[ -2  6  7

       2  -1  6] 

 Jan 5, 2016

Best Answer 

 #1
avatar+103061 
+10

A= [-3  5  -6

       9  -5  3]

 

B=[ -2  6  7

       2  -1  6] 

 

-3A  = [ 9    -15   18            6B =  [ -12   36    42

            -27   15   -9]                        12    -6    36 ]

 

-3A + 6B   =  [ 9 + -12     -15 + 36    18 + 42         =       [ -3      21      60

                      -27 + 12      15 + -6     -9 + 36]                   -15      9      27 ] 

 

 

 

cool cool cool

 Jan 5, 2016
 #1
avatar+103061 
+10
Best Answer

A= [-3  5  -6

       9  -5  3]

 

B=[ -2  6  7

       2  -1  6] 

 

-3A  = [ 9    -15   18            6B =  [ -12   36    42

            -27   15   -9]                        12    -6    36 ]

 

-3A + 6B   =  [ 9 + -12     -15 + 36    18 + 42         =       [ -3      21      60

                      -27 + 12      15 + -6     -9 + 36]                   -15      9      27 ] 

 

 

 

cool cool cool

CPhill Jan 5, 2016

34 Online Users

avatar
avatar
avatar
avatar
avatar